Upaya Menemukan Makna Hidup Tokoh Utama dalam Novel Hector and The Search For Happiness Perspektif Eksistensialisme Viktor Frankl - Rafika Dini; Engkin Suwandana; Taswirul Afkar (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to reveal the process of searching for life’s meaning undertaken by the main character in the novel Hector and the Search for Happiness by François Lelord through Viktor E. Frankl’s logotherapy theory. Modern life, characterized by routine, social pressure, and material achievement, often leads to a sense of meaninglessness (existential vacuum). The character Hector is portrayed as a successful psychiatrist who, despite his external accomplishments, feels unfulfilled. This research employs a qualitative-descriptive approach using close reading and content analysis of the novel’s narrative and dialogue. The findings indicate that the protagonist experiences an existential emptiness, prompting an inner journey through the three core values of logotherapy: creative value, experiential value, and attitudinal value. Hector’s journey reflects an existential transformation toward a more meaningful life. These findings demonstrate how literature can serve as a reflective medium for understanding the psychological dynamics of modern individuals facing a crisis of meaning.